Adherence and Persistence Patterns in Medication Use Among Men With Lower Urinary Tract Symptoms/Benign Prostatic Hyperplasia. (January 2017) - Shortridge, Emily; Donatucci, Craig; Donga, Prina; Marcus, Michael; Wade, Rolin L.
Medication adherence and persistence patterns among patients with lower urinary tract symptoms/benign prostatic hyperplasia (LUTS/BPH) were analyzed. Electronic medical records of patients from the Reliant Medical Group were examined to evaluate adherence and persistence patterns. A total of 1, 807 patients with LUTS/BPH were included in the study, and the number of patients at least 50 years of age was 1, 748/1, 807 (97%). Overall, 15.77% of patients were prescribed index prescription once, and no patients on combination alpha-blocker and 5-alpha reductase inhibitor therapies were prescribed their index prescriptions once. For all patients with LUTS/BPH, the mean number of prescriptions filled was 6.26, and the percentage of men persisting on index therapy for ≥4 years was 48%. Patients with LUTS/BPH showed a high proportion of both adherent and persistent treatment patterns, especially among patients taking combination therapy. The long follow-up time in our study provides evidence that patients are experiencing sufficient symptom relief to tolerate the challenges of remaining adherent and persistent.